THE STUDY OF IMPLICATURE AND HUMOROUS DEVICES OF DARK MEMES - Winanta Angesti; Priska Meilasari (Humaniora Scientia, 2021)
Memes are internet popular culture. They have so many topics, and one of them is darkhumor. Dark humor treats some taboo matters such as deformities, murder, suicide, disease,tragedy, pedophilia, and other in a cynical way. This research focuses on analyzing types ofimplicature and the humorous devices found in the dark memes; therefore, this study aims todiscover what kind of implicature is contained in the dark meme and what kind of humorousdevices that is used in the dark meme. This research is descriptive qualitative research, andthe data used in this research are dark memes and retrieved from reddit.com. The analysisshows that conversational implicatures and conventional implicatures are found in the darkmemes texts. There are some topics that are implicitly mentioned in the dark memes such asdeformities, necrophilia, sexual abuse, disease, murder, violence, stereotypes, pedophilia,death, tragedy, and suicide. Some humorous devices that are found in the dark memes areirony, satire, understatement, wit, aphorism, and sarcasm.Â Keywords: meme, dark memes, humor, implicature, humorous devices